2015
DOI: 10.1021/acs.cgd.5b00748
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Crystallographic Texture in Copper Foils Exhibiting Enhanced Mechanical and Electrical Properties by Pulse Reverse Electrodeposition

Abstract: The texture evolution in copper foils prepared by a rapid pulse reverse electrodeposition (PRED) technique using an 'additive-free' electrolyte and the subsequent correlation with the mechanical and electrical properties is investigated in the present study. Control over (111), (100) and (101) crystallographic textures in copper foils has been achieved by optimization of the pulse parameters and current density. Hardness as high as 2.0-2.7 GPa, while maintaining the electrical conductivity in the same range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 89 publications
3
26
0
Order By: Relevance
“…A few studies report on the crystallographic orientation of Zn deposits obtained with pulsed protocol (192,193). The correlation is, however, not straightforward, unlike what has been shown for Cu deposition-Strong (111), (100), and (101) textures can be achieved respectively by optimization of the pulse parameter (194). In light of the greater crystal anisotropy of Zn than Cu, we speculate that similar quality of texturing can be realized in Zn systems, which warrants further explorations.…”
Section: Approaches For Regulating Morphology Of Metal Electrodepositsmentioning
confidence: 72%
“…A few studies report on the crystallographic orientation of Zn deposits obtained with pulsed protocol (192,193). The correlation is, however, not straightforward, unlike what has been shown for Cu deposition-Strong (111), (100), and (101) textures can be achieved respectively by optimization of the pulse parameter (194). In light of the greater crystal anisotropy of Zn than Cu, we speculate that similar quality of texturing can be realized in Zn systems, which warrants further explorations.…”
Section: Approaches For Regulating Morphology Of Metal Electrodepositsmentioning
confidence: 72%
“…[61] Typically, the <111> components exhibit the lowest electrical resistivity for fcc metals and alloys. The effect of the <111> and <100> fiber-type texture formation on the electrical resistivity of copper wires has been discussed by Pavithra et al [62] and Moisy [47] and they found no significant effect. On the other hand, Ueda et al [60] showed that the electrical resistivity of cold-rolled cp-Ti is dependent on the formation of specific texture components.…”
Section: Formation Of Severely Deformed Layers In Areas Near the Imentioning
confidence: 99%
“…Although varying pulse reverse parameters leads to the notable evolution of plane orientation and crystal structure of all LMO-R samples, the most significant structural changes happen in the case of 79.17%LMO-R having higher crystallinity compared to the other samples. Apparently, the lowest value of f ′ applied to the electrodeposition of 79.17%LMO-R provides sufficient time to form more ordered plane orientation as a result of sluggish pulse alternation. , Basically, the meticulous adjusting of pulse reverse parameters (either lower values of f ′ or higher values of t c up to some extents) not only provokes the incorporation of Li + into MnO 2 lattice, but also can evidently affect the crystal structure evolution of Li x MnO 2 .…”
Section: Resultsmentioning
confidence: 99%